ISOLASI DAN KARAKTERISASI BAKTERI AMILOLITIK Bacillus sp. DARI TANAH RHIZOSFER DESA TEGALWATON KABUPATEN SEMARANG - Henokh Christian Prasgi; Theresia Avilla Jessica Puspitasari (Indigenous Biologi : Jurnal Pendidikan dan Sains Biologi, 2022)
Amylolytic bacteria have the ability to hydrolyze starch into glucose as an energy source for bacterial growth, can be found in terrestrial environments including the rhizosphere soil layer. Amylase enzymes are widely useful in industry, so exploration and research is needed related to bacteria that have amyolytic abilities. This study aims to isolate and characterize amylolytic bacteria of the genus Bacillus found in the rhizosphere soil of Tegalwaton Village, Semarang Regency. Methods carried out experimentally in the Microbiology Laboratory, Faculty of Biology, Satya Wacana Christian University include isolation and character tests of morphology, biochemistry and physiology. The results of the study contained 3 bacterial isolates with codes A1, A2 and A3 identified as Bacillus genus and have similarities with Bacillus thuringiensis, including in the amylolytic rods group bacteria, Gram positive and have spores. B. thuringiensis can ferment glucose, converting hydrogen peroxide (H2O2) into H2O and O2. Instead it cannot utilize citrate as a carbon source, it cannot oxidize glucose and forms acetyl methyl carbinol. Bacillus thuringiensis can be developed into an industrial strain for amylase enzymes. Molecular tests are needed to identify the specific species.